Long term study on blood glucose levels in wintering great tits Parus major in sites differing in artificial food availability - Adam Kaliński; Michał Glądalski; Marcin Markowski; Joanna Skwarska; Jarosław Wawrzyniak; Jerzy Bańbura; Piotr Zieliński (Scientific Reports)
Abstract Blood glucose concentration is one of the fundamental biochemical indices in the physiology of birds and other vertebrates. Since glucose serves as the main fuel for metabolic energy, its proper level in the blood serum is crucial to the individual in terms of physiological health, which leads to applying it as an ecophysiological indicator. Such an indicator may be especially useful during energetically demanding periods, such as winter at northern latitudes. Therefore, the main objective of this paper was to examine the variation in blood glucose in wintering the great tits (Parus major) in nine consecutive winters at two sites that differed with respect to the amount of human-provided food. We assumed that trophic conditions resulting from the use of artificial feeders that vary between sites across the years would affect the metabolic performance of birds and their physiological condition, which should be reflected in the blood glucose levels of wintering individuals. We showed that both females and males were characterised by significantly higher glucose levels at the study site, which was characterised by the high accessibility to human-provided food sources (forest clearing) than at the site with low and irregular artificial feeding. The difference remained distinct throughout most of the winter seasons of the study. We also revealed a substantial variation between seasons in blood glucose concentration in the case of male great tits. In general, we show that avian blood glucose can be used as an ecophysiological indicator of the trophic conditions of the environment in which individuals from small passerine species winter.